The Relationship between Management Practices of Nurse Supervisors and Patient Care Satisfaction (Journal of Basic and Applied Research in Biomedicine, 2022)
The study aimed to determine the relationship between management practices of nurse supervisors and patient care satisfaction. The study used a descriptive correlational through survey-questionnaire. Purposive sampling was utilized; there were 100 staff nurses and 100 patients who participated in this study. Results showed that the nurse supervisors’ management the over-all mean score is 4.02. For the over-all mean score for patient care satisfaction is 4.01. Further, Pearson-r revealed (r = 0.10, n = 200, p = 0.31) which indicated that there was no significant relationship between the two variables being tested in the study. Conclusions includes: staff nurses are generally contented with their supervisor’s management; patients are generally appeased with the nursing care they receive; management practice of nurse supervisors has no effect on patient care satisfaction.